Roles of Nucleoside Transporters and the Nucleoside Analogue Radiotracer 3’-Deoxy-3’-\([^18F]\)Fluoro-L-Thymidine (\([^18F]\)FLT) in PET Imaging of Cancer Cells - Irshad Ahmad; Nighat Nawaz; Saeid Afshar; Massoud Saidijam; Simon G. Patching (Medicine and Medical Research: New Perspectives Vol. 4, 2024)
The present study highlights nucleoside transporters in PET imaging of proliferating cancer cells using 3’-deoxy-3’-[18F]fluoro-L-thymidine. Nucleoside transport has an important role in maintaining the hyperproliferative state of most tumors and is therefore an important target for diagnostic and therapeutic agents in the detection, treatment and monitoring of cancers. Nucleoside transport proteins facilitate the transfer of physiological nucleosides and nucleoside analogue medications across biological membranes. Nucleoside transporters are key targets for therapeutic and diagnostic drugs used in the identification, management, and surveillance of cancers. They play a significant role in the maintenance of the hyperproliferative state of tumors in cancer. The nucleoside-based probe 3’-deoxy-3’-[18F]fluoro-L-thymidine ([18F]FLT) has been developed for PET imaging of proliferating cancer cells, which is less prone than 2-deoxy-2-[18F]fluoro-D-glucose ([18F]FDG) to non-specific effects. [18F]FLT enters proliferating cells through nucleoside transporters, then becomes phosphorylated and blocks DNA synthesis, whilst also becoming trapped inside the cell. Practicable and automated chemical syntheses of [18F]FLT have been developed, for which the most widely used radiolabelling precursor is the thymidine derivative 3-N-boc-5’-O-dimethoxytrityl-3’-O-nosyl-thymidine. Competitive cellular inhibition experiments with [18F]FLT suggested an involvement of hENT2 (in addition to hENT1) in the uptake of [18F]FLT in breast cancer cells, and also an involvement of hCNT1 and hCNT2. Further studies are required to investigate the potential role of hENT2 as a biomarker for breast cancer and to identify hENT2-specific inhibitors in targeted breast cancer therapy. [18F]FLT PET imaging has undergone feasibility studies and has been assessed in pre-clinical and clinical studies for the detection and diagnosis of various types of cancers and in monitoring their response to treatments. The roles of nucleoside transporters, especially ENT1, in the cellular uptake of [18F]FLT have been investigated.